2022
DOI: 10.3390/biomedicines10081914
|View full text |Cite
|
Sign up to set email alerts
|

Human Blood Serum Inhibits Ductal Carcinoma Cells BT474 Growth and Modulates Effect of HER2 Inhibition

Abstract: Trastuzumab, a HER2-targeted antibody, is widely used for targeted therapy of HER2-positive breast cancer (BC) patients; yet, not all of them respond to this treatment. We investigated here whether trastuzumab activity on the growth of HER2-overexpressing BT474 cells may interfere with human peripheral blood endogenous factors. Among 33 individual BC patient blood samples supplemented to the media, BT474 sensitivity to trastuzumab varied up to 14 times. In the absence of trastuzumab, human peripheral blood ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
(97 reference statements)
1
6
0
Order By: Relevance
“…The difference between SKBR3 and BT474 responses may be explained by the differential total expression of HER2, as well as the expression of EGFR and HER3 relative to HER2. BT474 expresses more HER2 ( ~ 2.8 × 10 6 copies per cell) 53 relative to SKBR3 ( ~ 1.2 × 10 6 copies) 54 . Both express HER3 to a similar level (1-1.2 × 10 6 copies) but SKBR3 expresses ~3-fold more EGFR (2.2 × 10 5 copies) than BT474 (7 × 10 4 copies) 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The difference between SKBR3 and BT474 responses may be explained by the differential total expression of HER2, as well as the expression of EGFR and HER3 relative to HER2. BT474 expresses more HER2 ( ~ 2.8 × 10 6 copies per cell) 53 relative to SKBR3 ( ~ 1.2 × 10 6 copies) 54 . Both express HER3 to a similar level (1-1.2 × 10 6 copies) but SKBR3 expresses ~3-fold more EGFR (2.2 × 10 5 copies) than BT474 (7 × 10 4 copies) 55 .…”
Section: Discussionmentioning
confidence: 99%
“…This result may be explained by the differential total expression of HER2, as well as the expression of Epidermal Growth Factor Receptor (EGFR) and HER3 relative to HER2. BT474 expresses HER2 to a greater extent (∼2.8 × 10 6 copies per cell) (Kamashev et al, 2022) relative to SKBR3 (∼1.2 × 10 6 copies) (Hendriks et al, 2013). Both express HER3 to a similar level (1-1.2 × 10 6 copies) but SKBR3 expresses ∼3-fold more EGFR (2.2 × 10 5 copies) than BT474 (7 × 10 4 copies) (Brockhoff et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of molecular pathways revealed that the addition of human serum reactivated MAPK signaling pathways inhibited by cetuximab alone [ 90 ]. Interestingly, human serum also modulated the effect of the HER2 monoclonal antibody trastuzumab on the HER2-overexpressing cell line BT-474 [ 223 ].…”
Section: Egfr-specific Therapeutic Monoclonal Antibodiesmentioning
confidence: 99%